Teaching of national peculiarities in business ethicsas an important part of training at higher technical educational institutions - Lapuzina, Olena Mykolayivna (ProQuest LLC, 2022)
The goal of the study is to show how university teachers can help students acquire knowledge and practical skills based on international and national business ethics. In accordance with this, training materials and a package of business cases were created. Based on the results of a conducted survey, the importance of knowledge and skills related to national differences in business communication was confirmed. The implementation of the author's course “National Peculiarities of Business Ethics” would be an effective tool for developing business communication skills of modern specialists.
Keywords: business ethics cases; national business ethics; critical thinking skills; qualified specialists; business ethics training